Encyclopedia of Finance - Lee, Cheng-Few.; Lee, Alice C.; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2013)
The Encyclopedia of Finance, Second Edition, comprised of over 1000 individual definitions and chapters, is the most comprehensive and up-to-date resource in the field, integrating the most current terminology, research, theory, and practical applications. Showcasing contributions from an international array of experts, the revised edition of this major reference work is unparalleled in the breadth and depth of its coverage. Part I provides readers with a basic framework for getting up to speed quickly, and has been updated to include over 200 new terms and essays. Part II features 24 new chapters and offers a more in-depth look at the topic through key developments and findings. Part III has also been expanded through the addition of four new appendices. From "asset pricing models" to "risk management," the Encyclopedia of Finance, Second Edition, serves as an essential resource for academics, educators, and students.
Part 1, Terms and Essays -- Part 2, Papers -- Part 3, Appendix -- Part 4, References -- Part 5, Index.
Keywords: Economics; Econometrics; Macroeconomics; Auditing; Economics/Management Science; Finance/Investment/Banking.; Accounting/Auditing.; Econometrics; Macroeconomics/Monetary Economics